Perlis ready to be catalyst to foster better border ties - Daily Express, (KK) (Daily Express (KK), 2014)
SATUN (Thailand): The Perlis government is willing to become the "middleman" or catalyst to enhance relations between states in Malaysia which share the border with southern Thailand.